Implementation Of Ship Certification Inspection By KSOP Class I Banten - Pabian, Dwi Aura; Nurul Muharani; Alivia Najwa; Salsa Amalia; Sonya Ritta Sitinjak; Alva Bagus PrihadhiLahagu; Syfia Fajar Maulani; Rubby Rahman Tsani (LPPM AKMI SUAKA BAHARI CIREBON, 2024)
In the waters of Banten, there are still many fishing vessels that should be required to have a certificate but do not have a certificate and have carried out shipping activities, the shipping activities carried out are illegal because they do not have a sailing permit, To get a sailing permit the ship owner must have a ship certificate. Therefore, the purpose of the study is to find out the implementation of ship inspection activities by marine inspectors at the Banten Class I Port Authority and Municipal Office, in order to find out what causes ships that do not have certificates. This study uses a descriptive qualitative method, as well as an interview method to obtain primary data through direct questions and answers with KSOP employees, and uses secondary data in the form of Ship Inspection SOPs and Study Literature. By increasing socialization about the importance of ship certification to ship owners through seminars, training, or socialization. KSOP can also expand information services through websites and call centers to make it easier for ship owners in the certification process.